RBP-J promotes cell growth and metastasis through regulating miR-182-5p-mediated Tiam1/Rac1/p38 MAPK axis in colorectal cancer - Li, Fang; Zhou, Ya-Dong; Liu, Jiao; Cai, Jiao-Di; Liao, Zhi-Ming; Chen, Guo-Qun (Cellular signalling, 2021)
RBP-J is involved in number of cellular processes. However, the potential mechanisms of RBP-J on colorectal cancer (CRC) development have not been clearly defined. In this study, we aimed to investigate the role and molecular mechanism of RBP-J in CRC. The expression levels of RBP-J and Tiam1 in CRC tissues and cells were evaluated by RT-qPCR or western blot. RBP-J was knocked down with sh-RBP-J or overexpressed by pcDNA3.1-RBP-J in CRC cells. Cell proliferation, migration and invasion abilities were analyzed by MTT, wound healing, and transwell assay, respectively. CHIP-qPCR, RIP and dual luciferase reporter assays were performed to confirm the interaction between miR-182-5p and RBP-J or Tiam1. Expression levels of p-p38 MAPK, p38 MAPK, Slug-1, Twist1 and MMP-9 were analyzed by western blot. G-LISA test was used to detect Rac1 activity. Our results showed that the expression of RBP-J and Tiam1 was significantly up-regulated in CRC tissues and cells. RBP-J overexpression promoted proliferation, migration and invasion of CRC cells. Moreover, RBP-J was found to directly target miR-182-5p promoter and positively regulate the Tiam1/Rac1/p38 MAPK signaling pathway in CRC cells. It was also proved that miR-182-5p can bind Tiam1 directly. Furthermore, experiments revealed that RBP-J could promote CRC cell proliferation, migration and invasion via miR-182-5p-mediated Tiam1/Rac1/p38 MAPK axis. In addition, knockdown of RBP-J reduced tumor growth and metastasis in CRC mice. RBP-J regulates CRC cell growth and metastasis through miR-182-5p mediated Tiam1/Rac1/p38 MAPK signaling pathway, implying potential novel therapeutic targets for CRC patients. •RBP-J and Tiam1 were dysregulated in colorectal cancer tissues and cells.•RBP-J promoted the growth and metastasis of colorectal cancer cells.•RBP-J positively regulated the Tiam1/Rac1/p38 MAPK signaling pathway.•RBP-J exerted its function via miR-182-5p-mediated Tiam1/Rac1/p38 MAPK axis.